Biotransformation and toxicity evaluation of functionalized manganese doped iron oxide nanoparticles. Issue 10 (15th February 2021) - Akhtar, Kanwal; Javed, Yasir; Muhammad, Faqir; Akhtar, Bushra; Shad, Naveed Akhtar; Sajid, Muhammad Munir; Jamil, Yasir; Sharif, Ali; Abbas, Wasim
Abstract: Safe inorganic nanomaterials are tremendously used for diagnosis and therapies. However, essential processing in the microbiological environment changed the physical properties and in situ degradability, which is evaluated meticulously. In this research article, bare, Polyethylene glycol, and citrate coated manganese doped iron oxide nanoparticles are synthesized through the coprecipitation route. Structural, magnetic, optical, and morphological analyses are performed through different characterization tools. X‐ray diffraction confirmed the formation of single‐phase FeMnO3 with a crystallite size of 48.91 nm. Vibrating sample magnetometer analysis confirmed the formation of soft ferromagnetic behavior of bare and coated nanoparticles (NPs). Scanning electron microscopy and transmission electron microscopy confirmed the formation of spherical shaped nanoparticles. Single‐dose in vivo acute toxicity testing is performed through the intraperitoneal route of administration on groups of healthy albino rats. Elevated enzyme levels of kidney and liver are observed at day 1 but a transient decrease is observed at later stages. Through optical follow‐up, degradation effects are studied by adding prepared NPs in lysosomal like medium. Finally, metabolization of degraded products based on manganese/iron ions is studied by adding apoferritin into a lysosome like solution. These studies showed partial storage of manganese ions from NPs, while no substantial transfer is observed in the case of manganese salt. Abstract : Manganese doped iron oxide nanoparticles have been prepared and functionalized using PEG and citrate polymers. Toxicity evaluation shows transient increase in different biochemical indicators. Transformation studies showed degradation of nanomaterials in the model lysosomal like medium and hinted the sequestering into degraded ions into ferritin proteins.